(ARTICLE RETRACTED) Empowering Disabled Economic MaqÄá¹£id Asy-SyarÄ«â€™ah Perspective in UD. Mutiara Handycraft Karangsari Buayan Kebumen Central Java - Akhmad Faozan (Ijtimā`iyya: Journal of Muslim Society Research, 2019)
This article is RETRACTED